Characteristics of Febrile Children Admitted to the ICU Following an Unscheduled ED Revisit Within 72 h, a Case–Control Study - Chiang, Charng-Yen; Chen, Yu-Lun; Lin, Yan-Ren; Cheng, Fu-Jen; Wu, Kuan-Han; Chiu, I-Min (Frontiers in Pediatrics, 2020)
Objective The purpose of this article was to demonstrate related characteristics of intensive care unit (ICU) admission after an unscheduled revisit by febrile children visiting the emergency department (ED). Method We performed a retrospective study in a tertiary medical center from 2010 to 2016. Patients whose chief complaint was fever and who were admitted to the ICU following a 72-hour return visit to the ED were included, and we selected patients who were discharged from the same emergency department for comparison. Results During the study period, 54 (0.03%) patients met the inclusion criteria, and 216 patients were selected for the matched control group. Regarding clinical variables on initial ED visit, visiting during the night shift (66.7% vs. 46.8%, p=0.010), shorter length of 1st ED stay (2.5 ± 2.63 vs. 3.5 ± 3.44 hours, p=0.017), and higher shock index (SI) (1.6 ± 0.07 vs. 1.4 ± 0.02, p=0.008) were associated with ICU admission following a return visit. On the return ED visit, we found that clinical variables such as elevated heart rate, SI, white blood cell count, and C-reactive protein level were all associated with ICU admission. Furthermore, elevated SI, pediatric age-adjusted (SIPA) values were observed in the study group in both the initial (42.2% vs 20.1%, OR:2.3 (1.37 - 4.31), p=0.002) and the return ED visit (29.7% vs 6.9%, OR: 4.6 (2.42 - 8.26), p<0.001). Conclusion For children who visited the emergency department with a febrile complaint, elevated SIPA values on the initial ED visit were associated with ICU admission following an unscheduled ED revisit within 72 hours.